The relationship between smoking and stroke: A meta-analysis. Issue 12 (March 2019) - Pan, Biqi; Jin, Xiao; Jun, Liu; Qiu, Shaohong; Zheng, Qiuping; Pan, Mingwo
Abstract: Background: Stroke is one of the leading causes of death and disability for adult men and women worldwide, and a number of studies have explored the influences of smoking on stroke. However, few studies have discussed the relationship between stroke and smoking with consideration of the following factors: sex, the number of cigarettes smoked per day, stroke subtype, and the follow-up duration. Consequently, we aimed to extend previous work by using a systematic review to explore the relationship between stroke and cigarette smoking in reference to the above factors. Methods: A systematic review was conducted using the PubMed, Embase, and Cochrane Central Register databases and the following search criteria: ["stroke" (MeSH) and "smoking" (MeSH)]. All analyses were conducted with Stata, and funnel plots and Egger regression asymmetry tests were used to assess publication bias. Results: The meta-analysis included 14 studies involving 303134 subjects. According to the meta-analysis, smokers had an overall increased risk of stroke compared with nonsmokers, with a pooled odds ratio (OR) of 1.61 (95% confidence interval [CI]: 1.34–1.93, P  < .001). A subgroup analysis conducted based on smoking status revealed ORs of 1.92 (95% CI: 1.49–2.48) for current smokers and 1.30 (95% CI: 0.93–1.81) for former smokers. In addition, the relationship between stroke of any type and smoking status was also statistically significant; current smokers had an increased risk of stoke compared with nonsmokers (OR: 1.46, 95% CI: 1.04–2.07, P  < .001), which was influenced by sex (men: OR: 1.54, 95% CI: 1.11–2.13, P  = .002; women: OR: 1.88, 95% CI: 1.45–2.44, P  < .023). From the analysis, we also observed that passive smoking increased the overall risk of stroke by 45% (OR: 1.45, 95% CI: 1.0–2.11, P  < .05). Based on the dose-response meta-analysis, the risk of stroke increased by 12% for each increment of 5 cigarettes per day.